Effects of probiotics supplementation on reducing inflammation in burn patients: Evidence based case report - Afifa, Nadhira Nuraini; Lestari, Wiji (Indonesian Nutrition Association, 2025)
Background: Burn injuries cause significant physical trauma and complex inflammatory responses, accounting for more than 300,000 deaths per year. Probiotics may help modulate inflammation in burn patients by improving biomarkers such as hs-CRP and IgA levels. This case report aims to investigate the effect of probiotics supplementation on reducing inflammation in burn patients. Methods & Materials: A literature search was on three large databases: PubMed, Cochrane Library, and Google Scholar. MeSH terms, advanced search, and eligibility criteria were used for title and abstract screening after removing duplicates. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Center for Evidence-Based Medicine. Results: Two randomized controlled trials (RCTs) met the PICO and eligibility criteria. One RCT found that probiotics supplementation significantly reduced hs-CRP levels (21.38 ± 44.45 vs 36.36 ± 79.03; p < 0.001) and improved wound healing in burn patients. The other RCT found that single and mixed strain probiotic administration significantly increased IgA levels (p < 0.001 and p = 0.025, respectively) in burn patients. Conclusions: Probiotics supplementation demonstrates significant benefits in reducing systemic inflammation and enhancing immune function. Further research is necessary to provide recommendations of probiotic use in burn care.